Long-term Care: Places to Call Home - Carolyn S. Wilken (EDIS, 2006)
FCS-2257, a 4-page fact sheet by Carolyn Wilken, is the first in a series on caregiving and aging. It will help elderly people and their caregivers learn about the many different kinds of long-term care and living assistance now available. Includes a visit checklist to fill out after visiting each facility. Also explains how costs are usually paid. Published by the UF Department of Family, Youth and Community Sciences, October 2006.